Peace through Equity: The Political Economy of Gender Discrimination in Land Property Rights in Enugu State, Nigeria - (:unkn) unknown (My University, 2013)
Conflicts over land in Africa have continued to be severe because of their scarcity in context of population growth, climatic change and as they are increasingly being commoditized. In another dimension, gender construction impacts differently on men’s and women’s access to land resource in most Nigerian traditional institutions, resulting to serious (gendered) social conflicts because this determines their opportunities for livelihoods or their impoverishment. This, on the other hand, poses serious development challenges to the country and African continent. This paper aims to investigate the persisting conflicts resulting from gender discrimination in land property rights of women in rural areas of Enugu State of Nigeria, and the roles of the state in the situation to entrench socio-economic development in the country.
Keywords: African Research